2020
DOI: 10.3390/molecules26010088
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Unifloral Honeys from SARDINIA (Italy) by ATR-FTIR Spectroscopy and Random Forest

Abstract: Nowadays, the mislabeling of honey floral origin is a very common fraudulent practice. The scientific community is intensifying its efforts to provide the bodies responsible for controlling the authenticity of honey with fast and reliable analytical protocols. In this study, the classification of various monofloral honeys from Sardinia, Italy, was attempted by means of ATR-FTIR spectroscopy and random forest. Four different floral origins were considered: strawberry-tree (Arbutus Unedo L.), asphodel (Asphodelu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…In our treatment, SVM was not useful. Ciulu et al [ 62 ] reported on the usage of ATR-FTIR spectra and processing by RF to this aim. Eighty samples belonging to four different floral origins were considered: strawberry tree, asphodel, thistle and eucalyptus.…”
Section: Discussionmentioning
confidence: 99%
“…In our treatment, SVM was not useful. Ciulu et al [ 62 ] reported on the usage of ATR-FTIR spectra and processing by RF to this aim. Eighty samples belonging to four different floral origins were considered: strawberry tree, asphodel, thistle and eucalyptus.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure fair trading of such high valued products as honey, an authentication system needs to be established to detect fraud in the honey supply chain. Most reported works on honey authentication mainly focus on the floral type (botanical origin) and geographical origins, and less frequently on entomological origins [10][11][12][13][14]. Few reported works have been reported on the honey authentication based on entomological origins [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Devi et al [17] also reported a satisfactory classification among multifloral and monofloral honey when ATR-FTIR was coupled with PCA. Finally, Ciulu et al [48] applied a random forest algorithm to the classification of 80 samples of asphodel, eucalyptus, thistle, and strawberry tree honey, thereby achieving an average accuracy of 87% in a cross-validation context.…”
Section: Stepwise Lda Based On Atr-ftir Spectramentioning
confidence: 99%